Bias and stereotyping among research and clinical professionals: Perspectives on minority recruitment for oncology clinical trials. Issue 9 (9th March 2020) - Niranjan, Soumya J.; Martin, Michelle Y.; Fouad, Mona N.; Vickers, Selwyn M.; Wenzel, Jennifer A.; Cook, Elise D.; Konety, Badrinath R.; Durant, Raegan W.
Abstract : Background: In recent years, extensive attention has been paid to the possibility that bias among health care professionals contributes to health disparities. In its 2003 report, the Institute of Medicine concluded that bias against racial minorities may affect communication or care offered. However, to the authors' knowledge, the role of bias within the context of recruitment of racial and ethnic minorities to cancer clinical trials has not been explored to date. Therefore, the authors assessed the experiences of clinical and research personnel related to factors influencing the recruitment of racial and ethnic minorities for cancer clinical trials. Methods: A total of 91 qualitative interviews were conducted at 5 US cancer centers among 4 stakeholder groups: 1) cancer center leaders; 2) principal investigators; 3) referring clinicians; and 4) research staff. Data analysis was conducted using a content analysis approach to generate themes from the transcribed interviews. Results: Five prominent themes emerged: 1) recruitment interactions with potential minority participants were perceived to be challenging; 2) potential minority participants were not perceived to be ideal study candidates; 3) a combination of clinic‐level barriers and negative perceptions of minority study participants led to providers withholding clinical trial opportunities from potential minority participants; 4) when clinical trial recruitment practices were tailored to minority patients, addressing research misconceptions to build trust was a common strategy; 5) for some respondents, race was perceived as irrelevant when screening and recruiting potential minority participants for clinical trials. Conclusions: Not only did some respondents view racial and ethnic minorities as less promising participants, some respondents reported withholding trial opportunities from minorities based on these perceptions. Some providers endorsed using tailored recruitment strategies whereas others eschewed race as a factor in trial recruitment. The presence of bias and stereotyping among clinical and research professionals recruiting for cancer clinical trials should be considered when designing interventions to increase minority enrollment. Abstract : Bias may impede the willingness of some clinical and research professionals to offer clinical trial enrollment to minority patients. Because a color‐blind approach may not be effective either, the authors suggest that a tailored recruitment strategy may increase minority participation in cancer clinical trials.